2023
DOI: 10.1007/s11094-023-02807-2
|View full text |Cite
|
Sign up to set email alerts
|

New Analytical Methods for the Determination of New Anti-Viral Drug Favipiravir: A Potential Therapeutic Drug Against Covid-19 Virus, in Bulk and Dosage Forms

Abstract: Simple, accurate and robust analytical methods have been developed and validated for the determination of favipiravir (FVPR) by RP-HPLC and UV spectroscopy techniques as per the ICH guidelines. In the RP-HPLC method for FVPR determination, the mobile phase was ammonium acetate buffer pH 6.5 in pump Aand methanol in pump B. The C18 (Sunfire) 5 μm, 4.6 × 250 mm column was used as a stationary phase, and the detection wavelength was at 323 nm. Under these conditions, FVPR was eluted as a sharp peak at 2.65 min an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Literature survey revealed that there were few analytical methods have been reported for the determination of favipiravir in pure drug and pharmaceutical dosage forms by using UV 1-5 , HPLC 6-13 , RP-HPLC [14][15][16][17][18][19][20][21][22][23][24] and HPTLC 25 so far. The aim of present work is to develop and validate a novel, rapid, simple, precise and specific Area under curve UV Spectrophotometric method for estimation of favipiravir in bulk and tablet dosage form.…”
Section: Fig1: Chemical Structure Of Favipiravirmentioning
confidence: 99%
“…Literature survey revealed that there were few analytical methods have been reported for the determination of favipiravir in pure drug and pharmaceutical dosage forms by using UV 1-5 , HPLC 6-13 , RP-HPLC [14][15][16][17][18][19][20][21][22][23][24] and HPTLC 25 so far. The aim of present work is to develop and validate a novel, rapid, simple, precise and specific Area under curve UV Spectrophotometric method for estimation of favipiravir in bulk and tablet dosage form.…”
Section: Fig1: Chemical Structure Of Favipiravirmentioning
confidence: 99%
“…However other anti-virals are estimated using different liquid chromatography techniques with green solvents such as gradient RP-HPLC-glibenclamide estimation using ethanol [7], Cefepime hydrochloride estimation using methanol [8], Rosuvastatin estimation using green solvent ethanol in RP-HPLC [9], Nevirapine and lamivudine using ethanol as solvent [10], Micellar chromatographic estimation of four antiviral drugs using Sodium Dodecyl Sulfate, Isopropanol, Triethylamine [11], Mixed micellar estimation of antiviral drugs using sodium lauryl sulfate [12] and other spectrophotometric-HPLC methods using green solvents [13] [14], famciclovir by RP-HPLC [15]. Certain green methods were reported using ethanol as a solvent for estimating nonantiviral drugs using HPLC such as deferasirox in human plasma [16], azosemide-micellar chromatography [17], impurities in deferasirox [18].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 As per the literature survey, it was known that analytical methods were developed for the estimation of favipiravir formulations. The developed methods included spectroscopic methods such as UV spectroscopic methods, [5][6][7][8][9][10] Visible spectrophotometric methods, 11 Fourier Transform Infrared Spectroscopic (FTIR) method, 12 spectrofluorimetric method, 13,14 chromatographic methods such as RP-HPLC methods, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] thin layer chromatography (TLC) 35 and hyphenated techniques such as UPLC-MS/MS methods, 36,37 LC-MS/MS methods [38][39][40][41][42] and electrical methods such as voltammetric methods. [43][44][45] But it was evident that only one method was developed for the estimation of favipiravir in pharmaceutical formulations using methyl orange and methyl red reagents in spectroscopy.…”
Section: Introductionmentioning
confidence: 99%